2013
DOI: 10.5603/cj.2013.0131
|View full text |Cite
|
Sign up to set email alerts
|

The co-application of hypoxic preconditioning and postconditioning abolishes their own protective effect on systolic function in human myocardium

Abstract: NE application, as compared to Control (30.35 ± 2.25 vs. 41.89 ± 2.25, 56.26 ± 7.73 vs. 65.98 ± 5.39, respectively). This was in contrary to the effects observed when IPC and POC were applied separately. Conclusions:The co-application of IPC and POC abolishes the cardioprotection of either intervention alone against simulated I/R injury in fragments of the human right heart atria. (Cardiol J 2013; 20, 5: 472-477)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…Nonetheless, the validity of this argument could be challenged, since it has been reported in the skeletal muscle of rats subjected to ischemia and reperfusion that the combination of IPreC and IPostC reduced glycogen depletion to a degree similar to that of IPreC alone whilst IPostC alone did not show protection [34]. Other investigators have observed a loss of protection in the human right atrial myocardium with the co-application of IPreC and IPostC [35]. Differences in the protocol and the animal model used may explain the discrepancy between these results but, certainly, this is an area of great clinical interest that would require further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the validity of this argument could be challenged, since it has been reported in the skeletal muscle of rats subjected to ischemia and reperfusion that the combination of IPreC and IPostC reduced glycogen depletion to a degree similar to that of IPreC alone whilst IPostC alone did not show protection [34]. Other investigators have observed a loss of protection in the human right atrial myocardium with the co-application of IPreC and IPostC [35]. Differences in the protocol and the animal model used may explain the discrepancy between these results but, certainly, this is an area of great clinical interest that would require further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial ATP-sensitive potassium channels (mKATP) control the activity of the mPTPs [13]. NO in low concentration was documented to be a potent mKATP opener through activation of anti-apoptotic cascade of enzymes called RISK pathway [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Сходные данные получили T. Roleder и соавт. [27]. Трабекулу, изолированную из правого предсердия человека, они подвергали воздей-ствию гипоксии (60 мин) и реоксигенации (60 мин) [27].…”
Section: данные экспериментов на изолированных препаратах сердца челоunclassified
“…[27]. Трабекулу, изолированную из правого предсердия человека, они подвергали воздей-ствию гипоксии (60 мин) и реоксигенации (60 мин) [27]. Тяжи соединительной ткани были получены во время операции АКШ у пациентов, средний возраст которых составлял 60 лет.…”
Section: данные экспериментов на изолированных препаратах сердца челоunclassified
See 1 more Smart Citation